Studio dei cromosomi mitotici e meiotici di Homarus gammarus (Crustacea, Decapoda) - SALVADORI, SUSANNA; COLUCCIA, ELISABETTA; CANNAS, RITA; DEIANA, ANNA MARIA; MILIA A (2002)
We studied the mitotic and meiotic chromosomes of Homarus gammarus(Crustacea, Decapoda). C-banding and AluI restriction enzyme banding have pointed out heterochromatic bands in most centromeric regions and in the short arm of some submetacentric chromosomes. The same short arms were brightly fluorescent after the AT-specific DAPI and Q fluorochrome bandings.